Do French Local Youth Policies Still Fail to Address Gender Issues? Lessons From the RAJE Project - Le Breton, Marie-Anaïs; Beaulieu, Thelma; Lecoq, Maxime; Loncle, Patricia; Mahamat, Maryam; Rault, Matthieu (SocietàMutamentoPolitica, 2025)
This article analyses the way in which gender issues are taken into account in the development of youth policies at a local level in France, and more specifically in three rural areas of Brittany. The study is being conducted through the “Recherche-Action, Jeunesses et Engagements” (RAJE) project, which has been running since January 2024. Involving decision-makers, youth workers and young people, it is an interesting field for understanding how gender issues emerge and are integrated on the youth policy agenda. Based on a collective narrative, this article both sheds light and questions the ways in which gendered subjectivities are interwoven with the engagement dynamics studied and experimented within the action-research. We analyze local situations in a reflexive and qualitative way, which allow us to formulate several hypotheses on the brakes and levers on putting gender issues on local policies’ agenda. Our work suggests that the gendered distribution of power in social contexts (both political and professional), the mechanisms of gender assignment, and the reproduction of heteronormative stereotypes are not only avenues of inquiry for our action-research, but also main ethical and political issues.